Pengaruh Strategi Pembelajaran Berbasis Proyek terhadap Hasil Belajar Siswa di Era Kurikulum Merdeka - Hijerah, Hijerah (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to analyze the effect of project-based learning strategies on student learning outcomes in the Merdeka Curriculum era. The Merdeka Curriculum emphasizes flexible, creative, and competency-oriented learning, so that project-based strategies are one of the relevant approaches to be implemented. This study used a quasi-experimental method with a pretest-posttest control group design. The research sample consisted of fifth-grade students at SDN 32 Banyuasin III who were divided into two groups: an experimental group using project-based learning strategies and a control group using conventional methods. The results showed that there was a significant increase in the learning outcomes of students taught using project-based learning strategies compared to the control group. In addition, this strategy also improves students’ critical thinking skills, collaboration, and independence in the learning process. These findings indicate that project-based learning can be an effective strategy in supporting the implementation of the Merdeka Curriculum, especially to achieve holistic and future-oriented learning objectives.